Small-angle neutron scattering and magnetization study of HoNi2B2C - Ramazanoglu, M.; Laver, M.; Yagmurcu, A.; Choi, E.-M.; Lee, S.-I.; Knigavko, A.; Gaulin, B.D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
The superconducting and magnetic properties of HoNi2B2C single crystals are investigated through transport, magnetometry and small-angle neutron scattering (SANS) measurements. In the magnetic phases that enter below the superconducting critical temperature, the small-angle neutron scattering data uncover networks of magnetic surfaces. These likely originate from uncompensated moments, e.g., at domain walls pinned to crystallographic grain boundaries. The field and temperature dependent behavior of SANS appears consistent with the metamagnetic transitions reported in earlier works.